2018
DOI: 10.5817/pedor2018-1-111
|View full text |Cite
|
Sign up to set email alerts
|

Analýza výzkumů vizuálií v učebnicích na příkladu učebnic s geografickým obsahem

Abstract: Abstrakt:Článek je přehledovou studií, jejímž cílem je vymezit a kriticky zhodnotit metodologické přístupy výzkumů vizuálií v učebnicích s geogra ickým obsahem. Dalším cílem této studie je shrnout hlavní závěry vědeckých prací a naznačit perspektivy budoucího výzkumu. V rámci odborných prací je zřetelná terminologická nejednotnost označení pro netextovou -ilustrační složku učebnic. Celkem bylo analyzováno 92 studií bez časové a územní speci ikace v českém a anglickém jazyce, které byly vyhledány v multioborový… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Další příčina absence výzkumu na primárním stupni vzdělávání může souviset i s personální poddimenzovaností oborově-didaktického vý-zkumu primární geografie. Problém určitého přehlížení primárního stupně vzdělávání v geograficko-didaktickém výzkumu se však neprojevuje jen ve výzkumu učebních úloh, nýbrž i v jiných výzkumných tématech, a to i v zahraničí (Řezníčková 2015, Bagoly-Simó 2018, Trahorsch, Bláha a Janko 2018.…”
Section: Diskuzeunclassified
“…Další příčina absence výzkumu na primárním stupni vzdělávání může souviset i s personální poddimenzovaností oborově-didaktického vý-zkumu primární geografie. Problém určitého přehlížení primárního stupně vzdělávání v geograficko-didaktickém výzkumu se však neprojevuje jen ve výzkumu učebních úloh, nýbrž i v jiných výzkumných tématech, a to i v zahraničí (Řezníčková 2015, Bagoly-Simó 2018, Trahorsch, Bláha a Janko 2018.…”
Section: Diskuzeunclassified
“…Visuals are part of the nonverbal component of textbooks, which is referred to in various ways across pedagogical, didactic and psychological research (compare Behnke, 2017;Janko & Knecht, 2013;Veriki, 2002). The overview study analysis methodical approaches to the research of visuals in geography textbooks performed by Trahorsch, Bláha & Janko (2018) identified a total of 20 special terms, 3 all of which are more or less synonyms of the term visual; as these terms are highly general and are based on general theories of visualisation and communication (Veriki, 2002;Spousta, 2007), it will be used further in this study. The subjectivity and ambiguity of depiction or illustration of the visualised phenomenon is a typical characteristic of visuals, as different authors may choose various means of expression (such as colour, symbol shapes, etc.).…”
Section: Visualisation Of Geographical Phenomena In Geography Textboomentioning
confidence: 99%
“…This type of study focuses on the analysis of latent content of visuals, which is often sidelined without adequate attention. We will therefore focus specifically on this form of analysis of visuals (Krippendorf, 2004;Trahorsch, Bláha & Janko, 2018). The analysis of latent content of communication (visuals) focuses on its depth structure compared to the analysis of manifestation content; the evaluator analyses the visual properties that are not obvious at first sight (for example, the analysis of manifestation content will focus on the categorization of visual types, but the analysis of latent content will focus on scaling the degree of fulfilment of visual quality criteria).…”
mentioning
confidence: 99%
See 2 more Smart Citations